The Importance of The Religious Pulpit As an Anti-Corruption Tool in Malang Society - Muhammad Amiruddin; Erryk Kosbandhono (Yayasan Adra Karima Hubbi, 2025)
Background. The existence of the Malang Raya government, with a majority Muslim population, should have the power to be the driving force for good, corruption-free governance. Islam supports the mission of social change and social criticism to create mutual awareness in the government bureaucratic system, educated and advocated through religious talks on a daily, weekly and monthly basePurpose. The aim of the study is to determine the views of Friday prayers in preventing the culture of corruption, and to determine the role of mosque and prayers in strengthening the mindset of the followers to respond to and combat corruption.Method. This field research uses a qualitative approach whose procedure is to produce descriptive data in the form of speech or writing and the behavior of the observed individuals. The preliminary study was conducted through initial interviews with informants and observations at the research site. Field notes resulting from observations, recordings, and notes from interviews are the result of the data collection phase. In the process of data analysis, there is data reduction, data presentation, and conclusion or verification.Results. This study shows that the perception of khatib against the danger of corruption through the religious pulpit includes (1) Friday sermon at Malang City Hall, saying that the religious pulpit is an important variable in the prevention of corruption in Malang City. (2) Friday khutbah. The Great Mosque of Baiturrahman, Malang Regency, saying that efforts to eradicate corruption are in line with dar'ul mafasid muqaddamun 'ala jalbil mashalih. (3) Friday Khutbah, An-Nuur Mosque Batu City provides a solution by playing a role, zuhud, patience, wara' and qana'ah are seen as more effective against corruption. In the mosque's activities and programmes, the study of corruption is not specifically discussed, but is embedded in various sermons and lecture topics. The materials presented tend to be thematic, such as fiqh worship, interpretation of Qur'an or Hadith, and other materials adapted to religious and national issues.